The constraints of youth: young people, active citizenship and the experience of marginalisation. Issue 3 (4th May 2019) - Hickey, Andrew; Pauli-Myler, Tanya
ABSTRACT: This paper charts the experiences of a group of young people and their involvement in a local government initiative to engage young people in public decision-making. Activated through a youth leaders' council that sought to influence and inform local government decision-making, the participating young people were given responsibility for enacting focus projects in collaboration with local government personnel. However, this method of simply bringing young people together with local government decision-makers did not automatically alter the way that decisions came to be made and ironically resulted in interactions that went some way to further reinforce existing perceptions of young people as incapable in situations of public administration. This paper reports on a case example detailing an interaction between the youth leaders and local government councillors, and will suggest that the experience of the young people involved in the youth leaders' council can be understood against a dynamic of 'constraint'.